Interorganizational Relationships Networks in Internationalization Process of Exporting Companies - Verdu, Fabiane Cortez; Reinert, Mauricio (Revista de Negócios, 2016)
This research aimed to characterize the interorganizational network of exporting companies in Maringá (PR). Social Network perspective is used to discuss the interorganizational relationship through concepts such as centrality, strong and weak ties, social embeddedness, embedded ties and arms-length ties. The population was 47 and the questionnaires were applied in 31 exporting companies, 66% of the population. When dealing with their relationships with organizations, the exporting companies concentrate their relationships on the value chain (buyers and suppliers). These relationships tend to be embedded and frequent, where each company plays only one role in relation to the other. Even though only four exporting companies cited theirs competitors as organizations with which they keep a more frequent contact, there is evidence of the existence of coopetition in these relationships. Eight exporting companies mentioned trade associations and companies formed by competitors as institutions with which they keep frequent contact, that is, these companies keep contact with competitors through institutions (evidence of the existence of coopetition). Limitations: The number of companies in the sample limits the statistical analysis. In trying to mitigate this problem, all the questionnaires were applied in loco assuring that the respondents were the correct informants. The number of variables in the ANOVA – GLM was limited to two, trying to keep the statistical power. As research suggestion, the population should be expanded. The role of institutions should be analyzed in depth, especially of the Mercosul Institute and the Banco do Brasil. The role of institution in the coopetition should be analyzed.